1995
DOI: 10.1002/path.1711760303
|View full text |Cite
|
Sign up to set email alerts
|

Absence of in situ hybridization evidence for latent ‐ or lytic‐phase Epstein‐Barr virus infection of preinvasive squamous lesions of the cervix

Abstract: To investigate whether Epstein-Barr virus (EBV) infection of the uterine cervix plays a significant role in cervical carcinogenesis, 30 preinvasive squamous lesions were subjected to in situ hybridization for (EBER-1,-2, and BHLF1) EBV transcripts which are expressed in latent and lytic infection, respectively. Twenty cases were known to contain EBV sequences by previous polymerase chain reaction (PCR) analysis. Irrespective of EBV PCR status or histological grade, none of the 30 cases demonstrated EBV transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
3
15
1
Order By: Relevance
“…In addition, recent reports indicate that EBV-specific PCR data need to be confirmed by morphological techniques. 28,29 The discrepancy between our present study and previous reports may therefore reflect differences in analytical methods.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, recent reports indicate that EBV-specific PCR data need to be confirmed by morphological techniques. 28,29 The discrepancy between our present study and previous reports may therefore reflect differences in analytical methods.…”
Section: Discussioncontrasting
confidence: 99%
“…In a ® rst attempt using in situ hybridization 5 biopsies from patients with detectable EBV DNA in cervical cell samples were examined but EBER positive cells were neither identi® ed in epithelial cells nor in B-lymphocytes. Similar negative results in cervical cancer and dysplasia have recently been published 20,22 . These results are contradictory to a previously published study by Landers and co-workers, who demonstrated EBV DNA in 43% in biopsies from cervical cancer by in situ hybridization technique 23 .…”
Section: Discussionsupporting
confidence: 75%
“…Since positive EBV analysis with PCR may derive from immortalized B-lymphocytes in the tissue, it is necessary to con® rm data from PCR analysis by morphological techniques, such as in situ hybridization, to show in which cells EBV is present 20 . Two short viral transcripts known as EBERs have been found to be expressed at high levels in most latent EBV infection 21 , although the absence of EBER does not exclude an EBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…A low EBV copy number less than 1 copy per cell was observed in cervical tumors, and EBER ISH positive cells were only detected in a subset of tumor nests (Sasagawa et al, 2000). Furthermore, EBV has been detected in normal squamous and glandular epithelial tissue adjoining the tumor and in B lymphocytes infiltrating the tumor or the stroma, and not in dysplastic or tumor cells, questioning whether EBV has any role in cervical cancer or is merely a passenger (Payne et al, 1995; Shoji et al, 1997). However, EBV may play an indirect role by interfering with the immune response to HPV-transformed cells through the production of the viral BCRF1 gene product, an interleukin-10 homolog (Al-Daraji and Smith, 2009; Polz-Dacewicz et al, 2016).…”
Section: Hpv and Herpesvirusesmentioning
confidence: 99%